The Linguistic Practice in the Construction of the Image of a Muslim Mother on Instagram - Arum Rindu Sekar Kasih; Suhandano; Aprilia Firmonasari; Nurdiyana Binti Abd. Ghani (UIN Raden Mas Said Surakarta, Indonesia, 2025)
In the era of social media, public figures do not merely share their personal lives but also construct self-image through linguistic practices that reflect social and religious identities. One such practice is sharenting, the act of sharing content about children or family life accompanied by specific narratives. Linguistic practices on social media, particularly sharenting by public figures, serve as a means of constructing and expressing intertwined social and religious identities. This study explores how language choices in the image captions of sharenting content posted by Oki Setiana Dewi, a Muslim celebrity known as both a preacher and a mother, reflect the construction of a Muslim mother identity in digital spaces. The research employs a qualitative sociolinguistic approach to analyze the language choices in the captions. The analysis reveals that the use of religious diction, prayerful expressions, and spiritual narratives serves as a linguistic strategy to affirm the mother's role as a moral educator and guardian of Islamic values within the family. Language functions not only as a means of conveying information but also as a tool for establishing social relations, constructing a religious self-image, and expressing the speaker's ideological position. Linguistic practices on social media can be understood as a means of representing Islamic identity while simultaneously reinforcing social credibility as a Muslim female public figure. Di era media sosial, figur publik tidak hanya membagikan kehidupan pribadi, tetapi juga membangun citra diri melalui praktik kebahasaan yang mencerminkan identitas sosial dan religius. Salah satu bentuknya adalah konten sharenting, yakni aktivitas membagikan kehidupan anak atau keluarga yang disertai narasi tertentu. Kajian ini berfokus pada takarir gambar (caption) dalam konten sharenting yang diunggah oleh Oki Setiana Dewi, seorang selebritas Muslimah yang dikenal sebagai pendakwah dan ibu. Dengan menggunakan pendekatan sosiolinguistik secara kualitatif, penelitian ini menelaah bagaimana pilihan bahasa dalam caption mencerminkan konstruksi identitas sebagai ibu Muslimah di ruang digital. Analisis menunjukkan bahwa penggunaan diksi religius, ungkapan doa, serta narasi spiritual menjadi strategi kebahasaan yang menegaskan peran ibu sebagai pendidik moral dan penjaga nilai-nilai Islam dalam keluarga. Bahasa tidak hanya berfungsi untuk menyampaikan informasi, tetapi juga membentuk relasi sosial, membangun citra diri religius, dan menunjukkan posisi ideologis pembicara. Dengan demikian, praktik kebahasaan dalam media sosial dapat dipahami sebagai sarana representasi identitas keislaman sekaligus upaya membangun kredibilitas sosial sebagai figur publik Muslimah.